PATIENTS’ SATISFACTION WITH CLINICAL LABORATORY SERVICES IN A SECONDARY HEALTH CARE FACILITY, ONDO WEST LOCAL GOVERNMENT AREA, NIGERIA (2015)
Patients’ satisfaction with clinical laboratory services is essential as laboratory service plays a key role in patient management. Under-utilisation which could be due to dissatisfaction of clinical laboratory services can contribute to a worsened state of morbidity or mortality among patients. Information on satisfaction with clinical laboratory services is essential for policy and development of interventions to improve patient’s satisfaction. This study was therefore conducted to assess patients’ satisfaction with the clinical laboratory services in a secondary health care facility in Ondo West Local Government Area, Ondo State. Using a cross-sectional study design, 426 patients utilising clinical laboratory services of the General Hospital, Ondo were recruited, using a systematic sampling technique. Respondents’ information was collected using pre-tested, semi-structured, interviewer-administered questionnaire. The questionnaire was used to obtain information on socio-demographic characteristics and satisfaction with the domains of clinical laboratory services (accessibility, hygiene of the environment, patient waiting time, patient-provider communication, availability of requested tests, and availability of laboratory space, competence and attitude of laboratory staff). Using the 50th percentile as cut-off, patients were classified as satisfied if they scored 50th percentile and above, while those scoring less than the 50th percentile were classified as dissatisfied. Chi-square test was used to determine the relationship between independent variables (sex, marital status, educational level) and the level of patients’ satisfaction. Logistic regression was used to determine predictors of patients’ satisfaction with the clinical laboratory services; level of significance was set at 5%. Respondents’ mean age was 34.7+12.4 years. Most of the respondents were females (62.4%), currently married (59.4%), Christians (87.1%), had secondary education (70.4%) and self-employed (51.4%). Majority of the respondents were satisfied with the confidentiality attached to the result of their tests (89.7%), the cost of the laboratory tests (67.6%), competence of the laboratory staff (78.0%), patient waiting time (81.9%) and the environmental hygiene of the laboratory (68.1%). Respondents also expressed satisfaction with the availability of space in the laboratory (84.5%), the availability of required tests (87.9%), patient-provider communication (77.2%), the respect and courtesy shown by laboratory staff (82.6%) and accessibility of the laboratory (71.8%). Overall, 79.0% of the patients were satisfied with clinical laboratory services. A significantly higher proportion of respondents who were males (61.6%), not married (64.6%) and had tertiary education (70.4%) were satisfied with the clinical laboratory services. Being male was found to be a predictor of patients’ overall satisfaction with clinical laboratory services (OR: 2.1; 95% CI: 1.1-4.3). Other predictors were not married (OR: 2.6; 95% CI: 1.2-4.1) and having a tertiary education (OR: 4.3, 95% CI: 2.1-6.5). Patients’ satisfaction with clinical laboratory services in the secondary health care facility was high. Subsidising the cost of laboratory tests, and improving the environmental hygiene of the laboratory could further improve patients’ satisfaction.